Neutral Diboron Analogues of Archetypal Aromatic Species by Spontaneous Cycloaddition. Issue 37 (4th July 2016) - Arrowsmith, Merle; Böhnke, Julian; Braunschweig, Holger; Celik, Mehmet Ali; Claes, Christina; Ewing, William C.; Krummenacher, Ivo; Lubitz, Katharina; Schneider, Christoph
Abstract: Among the numerous routes organic chemists have developed to synthesize benzene derivatives and heteroaromatic compounds, transition‐metal‐catalyzed cycloaddition reactions are the most elegant. In contrast, cycloaddition reactions of heavier alkene and alkyne analogues, though limited in scope, proceed uncatalyzed. In this work we present the first spontaneous cycloaddition reactions of lighter alkene and alkyne analogues. Selective addition of unactivated alkynes to boron–boron multiple bonds under ambient conditions yielded diborocarbon equivalents of simple aromatic hydrocarbons, including the first neutral 6 π‐aromatic diborabenzene compound, a 2 π‐aromatic triplet biradical 1, 3‐diborete, and a phosphine‐stabilized 2 π‐homoaromatic 1, 3‐dihydro‐1, 3‐diborete. DFT calculations suggest that all three compounds are aromatic and show frontier molecular orbitals matching those of the related aromatic hydrocarbons, C6 H6 and C4 H4 2+, and homoaromatic C4 H5 + . Abstract : B2 ‐aromatic : Uncatalyzed cycloaddition of nonpolar alkynes with B–B multiple bonds provides facile and selective access to novel 2 π‐ and 6 π‐aromatic and 2 π‐homoaromatic diboron analogues of C6 H6, C4 H4 2+, and C4 H5 + .